Internet encyclopaedia - revolution after Wikis - Stančić, Hrvoje (2008)
The aim of this paper is to classify encyclopedias according to the type of media and compare them. Encyclopedias are covering every theme that we can imagine. After appearance of the most popular online encyclopedia - Wikipedia, a small e-pedia revolution has begun. Today plenty of Wikipedia’ s clones, often called Wikis, can be found. Such type of encyclopedia enables own users free reading and editing. In spite of Wiki’ s popularity, there is always critics, fear and concern because of “ Wiki vandalism” . What is the future of encyclopedia, Wiki’ s advantages or spots? There are some new e-pedia projects, such as Googlepedia and Citizendium 2.0. The aim of new projects is to make improvements and to eliminate disadvantages of Wikipedia. After the analysis of the new online encyclopedia’ s project, results of the pilot study about using encyclopedias by students of the Faculty of Humanities and Social Sciences in Zagreb will be presented.